As ruralidades do Fundão : origens, valores sócioculturais e representações comunitárias no município de Araguari - MG - Borges, Jhonny de Oliveira (2006)
This research is the result of questionings made about the current condition of the rural community of Fundão, in the city of Araguari- state of Minas Gerais, which despite being one of its embryological nucleus of population, it is now found deserted. There has been a concern to develop a historical analysis. During investigation, it has been searched to clarify the inhabitation process of Fundão, the productive activities, social relations of production and cultural-religious practices which have been developed by its inhabitants. The principle on which it is based is the fact that to understand a current reality of a place, it is necessary to understand the transformations which it has gone through, throughout the historical process, mainly when country modernization has dismistified the idea of infertility in the cerrado (typical local vegetation). In the blossom of this process, rural exodus is almost an immediate consequence. Overall, on the farms and specifically in small properties, new production techniques have contributed to redesign social relations of production. In the case of the rural community of Fundão, before the use of these techniques provided by industrial activities, soil fertility loss, due to its inadequate and intensive utilization has led to changes in the productive processes. As a consequence, a substantial group of Fundão inhabitants moved to the city of Araguari. These socio-spacial changes engraved profound marks in the natural and cultural landscape of the place as well as in the everyday life of the people. As everything has happened at a rather fast pace, it has not always been possible for the people to adapt to the new imposed realities. But some aspects remain, principally in relation to belongings, for even those who have left Fundão to live in the city return motivated due to successive religious festivities in the community. Identifying the reasons which led people to leave Fundão it has been noticed that, although other productive processes have been installed, the place continues to be portrayed. Due to the festivity, a social net also arises to organize profane and religious events. The responsibility for holding festivities is shared with all the members of Fundão community, so as to guarantee its realization. Structural analysis of the rural community has been possible due to motivations and interests involved in the place reproduction. Although Fundão has gone through several productive processes which guaranteed subsistence of families, community maintenance is made possible through religious festivities. In this sense, it has been made necessary to take into consideration cultural and community aspects to understand the process which continues strengthening bounds between people and the place.